Have Euro Area Government Bond Risk Premia Converged To Their Common State? - Lorenzo Pozzi; Guido Wolswijk (Tinbergen Institute, 2008)
We derive a model in which a standard international capital asset pricing (ICAPM) model is nested within an ICAPM model with market imperfections. In the latter model an idiosyncratic stochastic factor affects the return of risky assets (over a risk-free rate) on top of the systematic component that is common to all countries (and that is interacted with a timevarying idiosyncratic “beta”). We introduce asymptotic convergence from the full ICAPM model with imperfections to the standard model by multiplying the idiosyncratic factor by convergence operators. The model is then estimated using the weekly 10 year government bond spreads of Belgium, France, Italy, and the Netherlands versus Germany over the period 1991-2006. We find that the idiosyncratic components have converged towards zero for all countries after the introduction of the euro implying that the efficiency of the euro area government bond markets under consideration has increased. Full convergence has not yet occurred however.
Keywords: E43; G12; 330; Government bonds; euro area; interest rate spreads; state space methods; Öffentliche Anleihe; Zinsstruktur; Zustandsraummodell; Belgien; Frankreich; Italien; Niederlande; Deutschland